Smart network anomaly detection software architecture for network-enabled ubiquitous devices - Mariusz Pelc; Galus, Dawid; Gola, Mariusz; Kawala-Sterniuk, Aleksandra (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
In this paper we present an architecture for run-time reconfiguration of network-enabled ubiquitous devices. The whole idea is based on a policy-based system where the whole decision-making (e.g. anomaly detection-related) logic is provided in a form of an externally loaded policy file. The architecture is verified through real-life implementation on an embedded system whose sensitivity can be easily modified should a need arise in run-time without affecting network device/segment (and thus potentially a number of network services) so that they continue working while the re-configuration process is triggered.